GPS equatorial ionospheric scintillation signals simulation, characterization, and estimation - Xu, Dongyang, author; Morton, Yu, advisor; Rino, Charles, committee member; van Graas, Frank, committee member; Pinaud, Olivier, committee member (Colorado State University. Libraries, 2019)
Strong equatorial ionospheric scintillation is characterized with simultaneous deep amplitude fading and fast phase fluctuations, which can severely degrade GNSS receiver performance and impact a variety of GNSS applications. This dissertation addresses the equatorial ionospheric scintillation effects on GNSS signals in three aspects: simulation, characterization, and estimation. The first part of the dissertation presents a physics-based, strong scintillation simulator that requires only two scintillation indicators as input parameters, with validation results using a large amount of real scintillation data. In order to improve the accuracy of carrier phase estimation, a semi-open loop algorithm is developed in the second part of the dissertation. The performance of this algorithm is evaluated using the developed simulator against two other state-of-the-art algorithms and shows improved performance in terms of reduced cycle slip occurrences and estimation error. In the third part, the scintillation signal characterization is conducted using a large amount of real strong scintillation data from Ascension Island. Statistical summaries are obtained, including the temporal characteristics of and correlation between fast phase changes and deep fades and the statistical relationship between the data bit decoding error occurrences and the intensity of amplitude scintillation.
Keywords: estimation; GPS signal simulation; atmospheric effects; ionospheric scintillation; GPS processing